Industrial product quality between accelerated design and traditional design (Al-Academy, 2025)
The research highlighted many developments that enabled design to undergo changes including a set of modern mechanisms and methods that helped it achieve quality. The research problem revolved around the following question: What is quality and its relationship to accelerated design and traditional design? The goal was to identify the requirements for achieving quality according to accelerated design and traditional design. From this, the importance of this study stemmed from its attempt to establish a conceptual framework to identify opinions that contribute to clarifying the difference between accelerated design and traditional design in terms of quality. The second chapter included two topics, the first of which was titled (The Concept of Quality in Product Design), and the second dealt with (The Concept of Accelerated Design and Traditional Design). Based on this, the researcher adopted indicators that were the result of the theoretical framework. The third chapter relied on following the descriptive comparative approach in the process of analyzing the samples. The fourth chapter included the results and conclusions, the most prominent of which were: All samples achieved a real ability in performance work in achieving design quality. In addition to creating a state of reliability and durability for the achiever and highlighting design quality. The most prominent conclusion was that the designs were effectively based on modern technological developments, presenting them as a design reality that highlights and achieves design quality through their performance dimension.